2012
DOI: 10.1111/cas.12025
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of Vmp1: Inhibition metastasis and proliferation of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the most deadly human cancers because of its high incidence of metastasis. Despite extensive efforts, therapies against metastasis of HCC remain underdeveloped. Vacuole membrane protein 1 (Vmp1) was recently identified to be involved in cancer-relevant processes; however, its expression, clinical significance and biological function in HCC progression are still unknown. Therefore, we evaluated the expression of Vmp1 in human HCC specimens. To functionally characterize V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Patients with low VMP1 expression had lower overall survival and disease-free survival than those with high expression of VMP1. Upregulation of VMP1 not only inhibited the proliferation of cancer cells, but also inhibited liver cancer cell metastasis in nude mice (11). The results of the present study and the results in breast and liver cancer are in accordance.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Patients with low VMP1 expression had lower overall survival and disease-free survival than those with high expression of VMP1. Upregulation of VMP1 not only inhibited the proliferation of cancer cells, but also inhibited liver cancer cell metastasis in nude mice (11). The results of the present study and the results in breast and liver cancer are in accordance.…”
Section: Discussionsupporting
confidence: 85%
“…It is well known that reduced levels of cell-cell adhesion proteins often correlate with tumor invasion and metastasis (22). Guo et al and other studies have shown that upregulation of VMP1 inhibits metastasis of tumor cells (11). However, to date, no studies have shown the impact of VMP1 in colorectal metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported to act as a tumor suppressor in a variety of tumors, including breast, 22 pancreas cancer, 23 as well as in hepatocellular cancer. 24 Because all five integration events categorized in this cohort were located in the intragenic region of TMEM49, it will be interesting to detect in the future whether this gene were commonly mutant in cervical cancers.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Normal VMP1 protein expression is necessary to maintain normal tissue homeostasis and integ-rity. 12 At present, a large number of studies have shown that VMP1 involves the development of many tumors, including hepatocellular carcinoma, 13,14 pancreatic cancer, [15][16][17] colorectal cancer, [18][19][20] ovarian cancer, 21 and breast cancer. 22 SNP rs1295925 was located in the p53 transcriptional binding region and its mutation might affect the binding of p53 and eventually lead to different tumor susceptibility.…”
Section: Discussionmentioning
confidence: 99%